Self-Disclosure dalam Kencan Buta: Peran Keterbukaan Diri Dalam Pembentukan Hubungan Awal - Qisthy Rabathy; Astri Auliya Nanda Purnama; Nazwa Latifa Maulida (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze the role of self-disclosure in the formation of initial relationships in the context of blind dating. Employing a qualitative approach with in-depth interviews, observation, and documentation, the study involved seven informants, comprising six blind date participants and one event initiator, selected through purposive sampling. The research focused on examining five dimensions of self-disclosure based on DeVito (1997): amount, value, accuracy & honesty, intention, and intimacy. The findings indicate that most participants felt comfortable disclosing light to moderately personal information, such as hobbies and educational background, which fostered an open conversational atmosphere. In terms of the value dimension, the shared information was deemed relevant for building emotional connections. Honesty (accuracy & honesty) was maintained by most participants, although some limited their disclosures for comfort reasons. The intention behind self-disclosure was generally to create a relaxed atmosphere and establish social bonds, while the intimacy dimension revealed emotional closeness through personal stories, such as family experiences or feelings of insecurity. The event initiator played a crucial role in creating a supportive atmosphere for openness by fostering an intimate and comfortable setting. The study concludes that self-disclosure in blind dating occurs in a purposeful and positive manner, contributing to the formation of meaningful initial relationships. Suggestions for future research include further exploration of cultural factors and gender dynamics in self-disclosure, as well as improvements in event organization strategies to facilitate more natural interactions.